A Strategist in Exile Xenophon and the Death of Thucydides - Nickel, Rainer (South Yorkshire Pen and Sword, 2016)
Thucydides was the chronicler of the almost 30-year long Peloponnesian war, which came to a close with Sparta's victory over Athens in 404 BC. His famous historical work was preserved, but ends abruptly many ears before the end of the war. It was continued decades later by Xenophon, with his "Greek history", Hellenica.
Keywords: Strategy